The study of the effect of bowel preparation agent on the quality of colonoscopy in Hospital USM Kubang Kerian - Alsakkaf, Arwa Adnan Abdullah (2021)
Background: Colorectal cancer is one of the most common cancers worldwide and Malaysia. Screening colonoscopy reduce overall incidence and death due to CRC. Proper bowel cleanliness is one of the main factors that directly affect the quality of the colonoscopy. The objective of our studies is to compare the effect of PEG versus OSP on the quality of colonoscopy measured by Boston bowel preparation score, cecal intubation rate, and total procedural time. Methods: This comparative cross-sectional study was conducted in November 2020 till February 2021 Universiti Sains Malaysia. A total of 171 patients underwent colonoscopy in the hospital endoscopy unit. 80 Patients received OSP, while 91 received PEG bowel preparation. All patients’ information such as age, gender, comorbidities, creatinine level, and indication for colonoscopy were recorded and saved. The quality indicators of colonoscopy including the efficiency of bowel cleanliness, the cecal intubation rate, and the total procedural time were compared between these two groups. For statistical analysis, categorical data was presented as frequency and percentage while numerical data was presented as mean and standard deviation (SD). We applied Independent t-test, chi square, Fisher exact and Simple Logistic Regression (SLR) appropriately in the univariate analysis. Then, we used Analysis of Covariates (ANCOVA) for objective one and three and multiple Logistic Regression (MLR) test to analyze our second objective. All assumptions for the tests were met. Results: Among 171 patients that underwent colonoscopy, 90 (52.6%) of them received Fortrans bowel preparation, and 81(47.4%) received fleet bowel preparation. 150 patients (87.7%) had a successful cecal intubation while, 21 patients